Epidemiologi Perdarahan Saluran Cerna Pada Pasien Endoskopi di Rumah Sakit Umum Daerah Cut Meutia, Aceh Utara, propinsi Aceh - Ikhsan, Maulana; Sayuti, Muhammad; Ariyanda, Iqbal; Akbar, Teuku Ilhami Surya (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Gastrointestinal bleeding is one of the main cause of death worldwide. For decades, the prevalence between lower gastrointestinal bleeding and upper gastrointestinal bleeding is constant. However, latest study showed that this may change due to the invention of new medication that prevent upper gastrointestinal bleeding. The epidemiology of gastrointestinal bleeding is important to plan the future promotion and prevention in the risk group and also to understand the distribution of the patient and their risk factor. The shortage of epidemiological data in developing countries makes the treatment of gastrointestinal bleeding became more challenging.Methods: This study is a retrospective study that aims to depict the epidemiology of gastrointestinal bleeding in patients who did gastroscopy or colonoscopy in Cut Meutia general hospital in North Aceh, Aceh Province. We analyze the medical record of the required patients in the interval of January 2019 to August 2021.Result: The incidence of lower gastrointestinal bleeding is higher than upper gastrointestinal bleeding. Female patients are dominant in develop gastrointestinal bleeding and elderly is the most common age that develop gastrointestinal bleeding.Conclusion : In general, the epidemiology of gastrointestinal bleeding in Cut Meutia general Hospital in North Aceh shares the same tendency with the incidence of gastrointestinal bleeding in many countries in the world, but there are several finding that differ such as high incidency of gastritic tumor and high incidency of gastritic tumor in younger age in male.